Mucosal melanoma of hard palate - Zahed Ali Qamer; Monika Maharjan; Kranthi Kumar Jandrasupalli; Bommisetty Lokesh; Amit Tyagi; Ravi Hari Phulware (University of São Paulo, 2024)
Melanoma arising in the hard palate is an exceedingly rare entity, comprising a minute fraction of all melanoma cases. The absence of specific clinical signs often leads to delayed diagnosis and subsequent challenges in treatment planning. We discussed the existing literature to elucidate the epidemiology, risk factors, and molecular pathways associated with melanoma of the hard palate. Additionally, we discuss the importance of a multidisciplinary approach involving dermatologists, otolaryngologists, oncologists, and pathologists in diagnosing and managing this condition. A 62-year-old male patient presented with a pigmented lesion on the hard palate mucosa, which was initially asymptomatic but gradually increased in size. Biopsy revealed melanoma, confirmed through immunohistochemical staining. Staging investigations indicated a metastatic disease. Surgery followed by adjuvant therapy was planned; however, he was lost for the follow-up. Melanoma originating from the hard palate mucosa is exceedingly rare, posing diagnostic and therapeutic challenges. Early detection, accurate diagnosis, and prompt multidisciplinary management are crucial for optimal outcomes. This case underscores the importance of comprehensive evaluation and tailored treatment strategies in patients with uncommon mucosal melanomas.